Estudio piloto del modelo técnico de ejecución del pitch a captura de pies en gimnasia acrobática - Leon-Prados, J. A.; Gonzalez Jurado, J. A.; Floria Martin, P. (Revista Internacional de Ciencias del Deporte, 2010)
In acrobatic gymnastics Toe Pitch to Catch (TPC) is one of the most traditional skill. The aim of the study was to provide a technical model of the skill to facilitate the understanding of the principal factors associated with the execution. In order to elaborate the model, 12 tryouts without technical deductions performed by a mixed pair of gymnasts were analyzed using techniques of photogrammetric and dynamometry. The movement was divided into three different phases for analysing purposes: Propulsion, Flight and Reception. Results indicated that maximum value of the force during the Propulsion Phase was 2,67 ± 0,06 BW, whereas during the Reception Phase the value obtained was 2,78 ± 0,30 BW. In the technical model analyzed highlights how in the Propulsion Phase is more important to optimize the impulse applied that the peak of force. During the Flight Phase, the high reproducibility in the successful attempts of the height reached by Top for facilitating its subsequent reception. Finally, during the Reception Phase, the braking action of Base in order to minimize the vertical reaction forces of floor for a movements receiving the Top.